Duration of and trends in respiratory support among extremely preterm infants. Issue 3 (10th November 2020) - Weisz, Dany E; Yoon, Eugene; Dunn, Michael; Emberley, Julie; Mukerji, Amit; Read, Brooke; Shah, Prakeshkumar S
Abstract : Objective: To evaluate annual trends in the administration and duration of respiratory support among preterm infants. Design: Retrospective cohort study. Setting: Tertiary neonatal intensive care units in the Canadian Neonatal Network. Patients: 8881 extremely preterm infants born from 2010 to 2017 treated with endotracheal and/or non-invasive positive pressure support (PPS). Main outcome measures: Competing risks methods were used to investigate the outcomes of mortality and time to first successful extubation, definitive extubation, weaning off PPS, and weaning PPS and/or low-flow oxygen, according to gestational age (GA). Cox proportional hazards and regression models were fitted to evaluate the trend in duration of respiratory support, survival and surfactant treatment over the study period. Results: The percentages of infants who died or were weaned from respiratory support were presented graphically over time by GA. Advancing GA was associated with ordinally earlier weaning from respiratory support. Year over year, infants born at 23 weeks were initially and definitively weaned from endotracheal and all PPS earlier (HR 1.06, 95% CI 1.01 to 1.11, for all outcomes), while survival simultaneously increased (OR 1.11, 95% CI 1.03 to 1.18). Infants born at 26 and 27 weeks remained on non-invasive PPS longer (HR 0.97, 95% CI 0.95 to 0.98 and HR 0.97, 95% CI 0.95 to 0.99, respectively). Early surfactant treatment declined among infants born at 24–27 weeks GA. Conclusions: Infants at the borderline of viability have experienced improved survival and earlier weaning from all forms of PPS, while those born at 26 and 27 weeks are spending more time on PPS in recent years. GA-based estimates of the duration of respiratory support and survival may assist in counselling, benchmarking, quality improvement and resource planning.